Adherence to iron-folic acid supplement and associated factors among antenatal care attending pregnant mothers in governmental health institutions of Adwa town, Tigray, Ethiopia: Cross-sectional study. - Tsgehana Gebregyorgis Gebremichael; Tsehaynesh Gidey Welesamuel (PLoS ONE)
Background Iron-folic acid supplementation during pregnancy is among the very effective interventions to prevent iron deficiency anemia, low birth weight, and prematurity. There is a need of having recent studies on adherence to the supplement that consider the very recent interventions targeted to scale up the use of iron-folic acid (IFA) supplement. Therefore we sought to assess adherence to IFA supplement and its associated factors among antenatal care attending pregnant mothers in governmental health institutions of Adwa town. Methods Institution-based cross-sectional study was conducted among 629 antenatal care attending pregnant mothers. Systematic random sampling method was used to select the study subjects. Data were collected through face-to-face interview and chart-review. Bivariable and multivariable binary logistic regression was computed. Variables with P-value <0.05 were considered statistically significant at 95% confidence interval (CI). Result Only 40.9% (95%CI: 37.0%- 44.7%) of participants were adherent (took four or more tablets per week). Women in the age group of 25-29 years [AOR: 2.22(1.21-4.07)] had increased odds of adherence as compared to those in the age group ≥ 35 years. Women who received nutrition counseling [AOR: 4.12(2.12-8.03)] and partner support [AOR: 2.23 (1.42-3.49)] had increased odds of adherence as compared to those who didn't receive nutrition counseling and partner support respectively. Similarly, women who had satisfactory knowledge on IFA supplement (AOR: 2.16(1.37-3.40)) had increased odds of adherence as compared to those who didn't have satisfactory knowledge on IFA supplement. Conclusion Adherence to the supplement was low. Efforts shall be done to improve awareness of pregnant mothers about IFA supplement through targeted nutrition counseling that includes the engagement of a partner.